Legal review of local government procurement of goods or services based on Presidential Instruction No. 1 Of 2025 (Study of the 2025 household budget of the Governor and Deputy Governor of Aceh) - Ahmad Maulana; Riza Afrian Mustaqim; Nahara Eriyanti (Priviet Social Sciences Journal, 2026)
Presidential Instruction No. 1 of 2025 represents a government initiative to enhance fiscal discipline and reduce the projected deficit of IDR 616.2 trillion (2.53% of GDP). The policy emphasizes budget efficiency through reductions in ministerial and agency spending by IDR 256.1 trillion and regional transfers by IDR 50.9 trillion, as outlined in Minister of Finance Letter No. S-37/MK.02/2025. This study examines the alignment between the 2025 Fiscal Year budget allocation for the household expenditures of the Governor and Deputy Governor of Aceh and the mandate of the Instruction. Using a normative juridical method with a regulatory approach, it analyzes relevant laws on regional financial management and government procurement. The findings reveal that the allocation by the General Affairs Bureau of the Aceh Provincial Secretariat has not fully reflected the principle of efficiency, as ceremonial and consumptive expenditures remain dominant and provide limited public benefit. From an administrative law perspective, this indicates inconsistency with principles of good governance, including efficiency, effectiveness, transparency, accountability, and public interest orientation. Such misalignment may lead to risks of administrative liability and abuse of authority. Strengthening oversight and reorienting budgeting toward public service outcomes are therefore essential.